KEDUDUKAN PEMBERIAN JAMINAN ATAS OBJEK MILIK ORANG LAIN YANG DIPEROLEH BERDASARKAN AKTA PENGIKATAN JUAL BELI - Putri, Elsha Ilham; embiring, Rosnidar Sembiring; Suprayitno, Suprayitno (Universitas Islam Sumatera Utara, 2024)
The fact that often happens that not a few Notaries / PPATs make mistakes, negligence, and ignore the laws and regulations so that in the end it causes problems in the future such as the case of granting guarantees on objects belonging to other people in Decision Number 2962 K / Pdt / 2019. The problems studied are the position of the sale and purchase object that has been transferred to another party, the position of granting collateral for the object that has been transferred and legal analysis of the application of the judge's law in the decision. The research method used is normative legal research which is presented descriptively. The research approach is carried out through the case approach method. Data sources are obtained from primary, tertiary and secondary legal sources. The data is analyzed through qualitative and deductive conclusions. The result of this research is that the seller who guarantees the object of sale and purchase that has been transferred to another party is an unlawful act because it violates the rights of others, contrary to the legal obligations of the perpetrator, contrary to decency and contrary to propriety in paying attention to the interests of self and property of others in the association of life. The granting of security over an object that has been transferred to another party results in the legal relationship to the land also shifting to the creditor. Keywords: Collateral, Property Rights, Sale and Purchase Binding Deed